웹상에서의 PIPO 경량 블록암호 구현 및 성능 평가 - 임세진(Se-Jin Lim); 김원웅(Won-Woong Kim); 강예준(Yea-Jun Kang); 서화정(Hwa-Jeong Seo) (한국정보통신학회논문지, 2022)
PIPO is the latest domestic lightweight block cipher announced in ICISC'20, which is characterized by being lightweight to facilitate implementation on IoT with limited resources. In this paper, PIPO 64/128-bit and 64/256-bit were implemented using web-based languages such as Javascript and WebAsembly. Two methods of performance evaluation were conducted by implementing bitsice and TLU, and the performance was compared by implementing Looped written using for statements and Unrolled written for statements. It performs performance evaluations in various web browsers such as Google Chrome, Mozilla Firefox, Opera, and Microsoft Edge, as well as OS-specific environments such as Windows, Linux, Mac, iOS, and Android. In addition, a performance comparison was performed with PIPO implemented in C language. This can be used as an indicator for applying PIPO block cipher on the web. PIPO는 ICISC'20에서 발표된 최신 국산 경량 블록암호로, 리소스가 제한된 IoT 상에서 구현하기 용이하도록 경량화 되어있다는 특징이 있다. 본 논문에서는 자바스크립트(Javascript), 웹어셈블리(WebAssembly)와 같은 웹 기반 언어를 사용하여 PIPO 64/128비트, 64/256비트를 구현하였다. PIPO의 비트슬라이스(BitSlice)와 TLU를 구현하여 성능평가를 진행하였으며 for문을 사용하여 작성한 일반 루프(Looped)와 for문을 풀어 작성한 루프 풀기(Unrolled)도 구현하여 성능을 비교했다. Google Chrome, Mozilla Firefox, Opera, Microsoft Edge와 같은 다양한 웹 브라우저와 윈도우즈, Linux, Mac, iOS, 안드로이드와 같은 OS별 다양한 환경에서 성능평가를 수행한다. 또한 C언어로 구현된 PIPO와 성능 비교도 수행하였다. 이는 웹상에서의 PIPO 블록암호 적용을 위한 지표로 사용될 수 있다.